Beyond words: an exploration of free-hand sketches and EEG-based neurobiological signatures to unveil the underlying depression among cancer patients - Miami, Anika Tahsin; Mrittika, Anika Priodorshinee; Hossain, Syed Zuhair (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.